The Influence of Fintech Management, Financial Literacy, Investment Knowledge, and Investment Motivation on Investments of Students - Rifki Alfiansyah; Muslimin (JIEMAN: Journal of Islamic Educational Management, 2025)
This study explores the influence of financial technology, financial literacy, investment knowledge, and investment motivation on investment decisions among undergraduate accounting students at public universities in Surabaya. Amid the rapid growth of financial technology and its widespread use among young adults, understanding the key determinants of students’ investment behaviour has become increasingly relevant in contemporary financial markets. Adopting a quantitative approach, data were collected through a structured survey and analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) to assess both the measurement and structural models. The findings reveal that financial literacy, investment knowledge, and investment motivation have a significant and positive effect on investment decisions, whereas financial technology does not show a significant influence. These results suggest that, despite the increasing availability of technological tools, effective investment decision-making is more strongly shaped by individual competencies and motivational factors. Accordingly, the study highlights the importance of strengthening financial education and enhancing students’ financial and digital competencies to promote more informed, rational, and confident investment behaviour among future accounting professionals.